3D PdPb nanochain networks with efficient catalytic performance for ethylene glycol electrooxidation. (12th September 2022) - Zou, Bin; Zhang, Yangping; Gao, Fei; Li, Zhuolin; Wang, Caiqin; Wu, Zhengying; Wang, Dongqiong; Du, Yukou
Abstract: The noble metal anodic catalysts with three-dimension (3D) chain-like network structure have been researched thoroughly due to their unique morphological characteristics. Herein, a novel scheme has been designed rationally to synthesize 3D PdPb nanochain networks (PdPb NCNs). Numerous nanochains were interlaced and stacked to form the nanonetworks, which were contributed to improving electrocatalytic performance. Abundant steps and kinks existed on the nanochain networks, which provided plentiful active sites to improve the electrocatalytic activity. In the subsequent electrochemical tests, the mass activity of Pd65 Pb35 NCNs was 4.47 A mg pd −1, higher than other catalysts. Moreover, in the chronoamperometry and consecutive CV measurements, Pd65 Pb35 NCNs exhibited the best stability than other prepared samples. This work explored the rational synthesis of PdPb nanochain networks, and confirmed the excellent electrocatalytic performance in EGOR. Graphical abstract: Image 1 Highlights: The intertwined nanochain network structure was beneficial to optimize the electron transport process. The catalyst components were optimized by controlling the amount of Pb(HCOO)2 . Pd65 Pb35 NCNs displayed the excellent electrocatalytic activity and stability in EGOR.